EFFECT OF LOCAL VIBRATION ON ROAD CYCLISTS - Ciekurs, Kalvis; Krauksts, Viesturs; Krauksta, Daina; Grants, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In sprint distance probably the most important factor for a good result is the athletes achievements in power of cycling, because the athletes, who ride with a very high frequency, but cannot put in a cycle solid force in competitions. Consequently is need for new resources or means to increase the strength expressions, to be able to compete successfully with high-level athletes. One of such is the local vibration. In our study we use the local vibration in development of cyclists strength expressions and power the aim of study is to determine influence of local vibration on cyclists peak anaerobic power. The subject of study is 15years old 2 cyclists. To carry out experiment, we arranged both cyclists, was made an anaerobic power test, when the athletes were given an unlimited time to warm up and achieve the highest possible power. Maximum power test results before the local vibration showed that the average power of the test group was 906 W, after application of local vibration peak power was 975W. A study has confirmed our allegation that application of local vibration can significantly improve the results of sprint cycling. Local vibration as an innovative training mean has proved its reliability in training process, as the random-level athletes improve their anaerobic power.